Nursing students’ quality of life - Araujo, Marcos Antonio Nunes de; Lunardi Filho, Wilson Danilo; Leite, Lucas Rasi Cunha; Ma, Regiane Tu Kun; Silva, Anderson Aparecido da; Souza, José Carlos (Rev Rene, 2014)
One aimed to evaluate the quality of life of nursing students from a public university from Dourados, MS, Brazil. This is an exploratory, descriptive and cross-sectional study conducted in October and November 2011 through the demographic and quality of life questionnaires SF-36. Out of the 102 students who participated in the study, 91.0% were between 18 to 23 years old, 49.01% had financial support from their parents of up to two minimum wages, 89.5% were single, 98.7% did not work. Nursing students from the 3rd and 2nd year had the lowest scores for quality of life and students from the 1st and 4th years had the highest scores. Changes were detected in the areas Physical Aspect (p=0.002), Mental Health (p=0.010), Social Aspect (p=0.002), Emotional Aspect (p=0.001) and General Health State (p=0.001). It is concluded that female students who are attending the intermediate years have low quality of life.